Heroines, Hierarchies, and Space: The Fiction of Cecilia Absatz - Naomi Lindstrom (Studies in 20th & 21st Century Literature, 2010)
This examination of the fiction of Cecilia Absatz (Argentina, 1943), covers three novels: Féiguele (1976), the 1982 Té con canela ‘Tea with cinnamon’ and the 1985 Los años pares ‘The Even-Numbered Years.’ The continuities between the three texts, and especially the similarity of their female protagonists, who age from adolescence to the threshold of middle age, allow these novels to be read as a series. The primary focus of this study is the maturation of the protagonists as they struggle for autonomy while navigating different types of space. These include space that is marked by gender; identified as Jewish; and dominated by members of various elites, whether defined by wealth and lineage, by celebrity, or by specialized cultural knowledge or skills. The protagonists are at a disadvantage in different environments: being female in a corporate workplace dominated by powerful males; craving individuality and solitude in a Jewish space in which community is the ideal; and being barely middle-class in milieux where money, accomplishments, and social connections are crucial. Though in many episodes the heroines, out of insecurity and inexperience, allow themselves to be intimidated and manipulated, they analyze their experiences, learn, and seek to strengthen their autonomy. Only in the third of the novels does the protagonist succeed in breaking the hold that more powerful and prestigious men hold over her and establishing a space for herself.
Keywords: Cecilia Absatz; Féiguele; Té con canela; Tea with cinnamon; Los años pares; The Even-Numbered Years; female protagonists; adolescence; middle age; autonomy; space; navigating space; jewish identity; gender identity; class identity; gender conflict; gender struggles